Generating Live Soccer-Match Commentary from Play Data - Taniguchi, Yasufumi; Feng, Yukun; Takamura, Hiroya; Okumura, Manabu (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
We address the task of generating live soccer-match commentaries from play event data. This task has characteristics that (i) each commentary is only partially aligned with events, (ii) play event data contains many types of categorical and numerical attributes, (iii) live commentaries often mention player names and team names. For these reasons, we propose an encoder for play event data, which is enhanced with a gate mechanism. We also introduce an attention mechanism on events. In addition, we introduced placeholders and their reconstruction mechanism to enable the model to copy appropriate player names and team names from the input data. We conduct experiments on the play data of the English Premier League, provide a discussion on the result including generated commentaries.